KORELASI ANTARA VARIABEL DEMOGRAFI DENGAN TINGKAT ADOPSI E-BANKING - SRI WIDIYATI SOEMODIPOERO (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
Abstract Service innovations that have been carried out by banks will succeed depending on the intention of adoption and the intention of loyal customers in using E-Banking.The higher the intention of adoption and the intention of loyalty towards banking innovation, the stronger the banking system, the financial system is not easily fragile and the national economy is stronger. The research problem is how the correlation between demographic variables with the level of adoption of E-Banking. Sampling is purposive sampling and data is collected by using a questionnaire. Data analysis using cross tabulation and using Chi Squared. Statistical test results show that gender and education level do not correlate with E-Banking adoption rates while age and occupation variables have a correlation with E-Banking adoption rates. Keywords: E-Banking, adoption rate, demographic variables, Chi-Squared